128 Quantification of glutamate in the grey matter and its relationship with cognitive performance in multiple sclerosis. Issue 3 (9th February 2012) - Muhlert, N; Atzori, M; De Vita, E; Thomas, D; Geurts, J J; Wheeler-Kingshott, C A; Thompson, A J; Ciccarelli, O
Abstract : We aim to assess whether the concentration of glutamate, an excitatory neurotransmitter, changes in the grey matter (GM) of patients with Multiple Sclerosis (MS), and whether it relates to cognitive dysfunction and disability. Single-voxel MRS was performed at 3T in 18 patients with relapsing-remitting MS [12 women, age 43.5 years, median EDSS 2.8] and 17 healthy subjects [11 women, age 39.7] in the right cingulate and parietal cortices, right hippocampus and thalamus. (Abstract 128 figure 1 ) Visual and verbal memory and speed of information processing were assessed. Patients showed significantly worse performance on the visual memory test, verbal learning, delayed verbal recall, and speed of information processing, compared to controls. Patients showed lower glutamate concentration in the cingulate and parietal cortices and in the hippocampus compared to controls. Patients showed significantly lower N-Acetyl-Aspartate levels in the thalamus and cortical GM, and reduced glutamate-glutamine, choline-containing compounds and creatine plus phosphocreatine levels in the cortical GM, compared to controls. Lower hippocampal glutamate levels correlated with worse visual memory. Reduced glutamate levels in the cingulate cortex and thalamus correlated with worse speed of processing and visual memory, respectively. We found reduced glutamate neurotransmission in the cortical and hippocampal regions, which was linked to cognitive impairment. Reduced levels of most of the metabolites in the cortical GM, together with normal Inositol, are in agreement with post-mortem findings of GM neuronal loss, modest glial proliferation, low degree of inflammation and energy metabolism.